Validity of protein-creatinine and protein-osmolality ratios in the estimation of massive proteinuria in children with nephrotic syndrome - M. Sukmawati; K. Suarta (Paediatrica Indonesiana, 2007)
Background Children with nephrotic syndrome have massiveproteinuria, a rate of excretion equal to or greater than 40 mg/hour/m 2 body surface. The ability to quantitate massive urinaryprotein excretion is very important for both diagnostic andprognostic purposes. Quantification of proteinuria using 24-hoururine collection (Esbach) is difficult to do especially in children;moreover, many false-positive and false-negative results arereported for any semi-quantitative methods such as dipstick andsulfosalicylic acid measurement.Objective To determine the accuracy of protein-creatinine ratio(PCR) and protein-osmolality ratio (POR) in quantification ofmassive proteinuria in children with nephrotic syndrome.Methods Diagnostic tests were conducted on children withnephrotic syndrome aged 2-12 years with Esbach as a referencestandard. Sensitivity, specificity, positive predictive value (PPV),negative predictive value, (NPV), pre and posttest probabilitywere compared between PCR and POR.Results Study patients consisted of 47 children, 38 (81%) withmassive proteinuria. PCR has sensitivity of 92%, specificity of78%, PPV of 95%, NPV of 70% and posttest probability of 95%.POR has sensitivity of 76%, specificity of 78%, PPV of 94%, NPVof 44% and posttest probability of 94%.Conclusion Both PCR and POR are accurate to determine massiveproteinuria in children with nephrotic syndrome.